2022
DOI: 10.3389/fnagi.2022.1000707
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of napping in older adults: A systematic review

Abstract: A growing body of evidence indicates that napping is common among older adults. However, a systematic review on the effect of napping on the elderly is lacking. The aim of this systematic review was to (i) determine how studies evaluated napping behavior in older adults (frequency, duration and timing); (ii) explore how napping impacts perceptual measures, cognitive and psychomotor performance, night-time sleep and physiological parameters in the elderly (PROSPERO CRD42022299805). A total of 738 records were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…They were controlled by two experimenters during the experiment and were awakened by an alarm placed next to the bed. Upon awakening, the participants rated their sleep quality during the nap on a 100-mm visual analog scale (Monk, 1989), ranging from 0 (no sleep at all) to 100 (deep, uninterrupted sleep), with no specific cut-off point that indicated sleep (Romdhani et al, 2021a;Souabni et al, 2022b). Participants who were unable to initiate sleep, as indicated by a score of 0 on the visual analog scale, were excluded.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…They were controlled by two experimenters during the experiment and were awakened by an alarm placed next to the bed. Upon awakening, the participants rated their sleep quality during the nap on a 100-mm visual analog scale (Monk, 1989), ranging from 0 (no sleep at all) to 100 (deep, uninterrupted sleep), with no specific cut-off point that indicated sleep (Romdhani et al, 2021a;Souabni et al, 2022b). Participants who were unable to initiate sleep, as indicated by a score of 0 on the visual analog scale, were excluded.…”
Section: Experimental Designmentioning
confidence: 99%
“…NREM plays a role in cellular 13.6 ± 1.3 #+++** 9.7 ± 1.4 ###+++£** 11.8 ± 1.4 ###+++£** ESS (au) 6.5 ± 1.3 7.4 ± 0.6 5.1 ± 1.02 ++£ 6.4 ± 0.9** 3.8 ± 0.7 # 5.2 ± 0.9 6.2 ± 0.9 ##+++£££ 6.9 ± 0. Frontiers in Physiology frontiersin.org repair, memory consolidation, motor skill recovery, and learning (Souabni et al, 2022a). Furthermore, naps may be associated with higher parasympathetic activity (Chen et al, 2020) that benefits executive functions.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analysis showed that naps without definite timing were significantly associated with an increased risk of depression, while an afternoon nap trended toward an increased risk of depression but was not statistically significant. Opposite results were also obtained: a nap after lunch was a protective factor against depression (Souabni et al, 2022) and cognitive flexibility (Slama et al, 2015). A review in 2021 also found that an early afternoon nap (post-lunch dip time) improved cognitive performance and work efficiency (Dutheil et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…A meta-analysis based on experimental studies in working-aged adults showed that cognitive performance increased after napping and that timing rather than duration influenced cognitive performance (Dutheil et al, 2021 ). Based on scientific evidence, the benefits of napping on psychomotor performance and learning abilities in older adults have also been discovered (Souabni et al, 2022 ). Cognitive impairment is an important symptom and outcome indicator of depression.…”
Section: Introductionmentioning
confidence: 99%